Mitybos poveikis Lietuvos didelio meistriškumo sportininku raumenu masei - Baranauskas, M.; Jablonskiene, V.; Abaravicius, J. A.; Arlauskas, R.; Stukas, R. (Sporto Mokslas-Sport Science, 2020)
For better athletic performance, athletes need to develop relatively high muscle mass. The anabolic effect of dietary amino acids on newly synthesized muscle proteins depends on the amount of protein intake and the qualitative amino acid composition of food rations. Due to the insufficient availability of endogenous essential amino acids, the rate of muscle protein synthesis may be reduced. The aim of the study was to evaluate the effect of Lithuanian high performance athletes` diet on muscle mass hypertrophy.Lithuanian high performance athletes aged 18.0± 3.3 years (n= 323) were studied. Measurements of athletes` muscle mass were performed using the BIA tetra-polar electrode method. The actual nutrition study was conducted using the 24-hour food recall method.The amounts of protein and carbohydrates intake by athletes are 1.7± 0.6g/kg and 5.5± 2.1g/kg of body weight, respectively. The amounts of all essential amino acids consumed by athletes are higher than recommended. The 5.5 kg increase in muscle mass of athletes is due only to the consumption of higher protein content (95% CI: 1.0; 10.1; p= 0.016). Regardless of carbohydrate intake, the increased muscle mass of athletes is largely due to increased protein and amino acid intake. Increased intake of the amino acids leucine, valine, and arginine has a positive effect on muscle mass gain, but potentially unbalances the qualitative composition of amino acids in athletes` diets.